Spatial modeling in technology adoption decisions: the case of shuttle train elevators (2005)
This article empirically models a strategic game of technology adoption of shuttle train grain elevators with information on location of the firm and its competitors. A spatial econometric model illustrates the role of spatial interdependence of rivals’ decisions as well as agronomic and competitive variables on discrete adoption decisions. The analysis assesses equilibria conditions that characterize technology adoption, in this case of shuttle train adoption, and the results provide an explanation of shuttle train adoption decisions in the grain handling industry in which spatial competition is critical.